2019
DOI: 10.1096/fj.201802442rr
|View full text |Cite
|
Sign up to set email alerts
|

Post‐translational acylation controls the folding and functions of the CyaA RTX toxin

Abstract: The adenylate cyclase (CyaA) toxin is a major virulence factor of Bordetella pertussis, the causative agent of whooping cough. CyaA is synthetized as a pro‐toxin, pro‐CyaA, and converted into its cytotoxic form upon acylation of two lysines. After secretion, CyaA invades eukaryotic cells and produces cAMP, leading to host defense subversion. To gain further insights into the effect of acylation, we compared the functional and structural properties of pro‐CyaA and CyaA proteins. HDX‐MS results show that the ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Importantly, a significant amount of heterogeneity was observed in the acylation patterns of LtxA (Fong et al, 2011), but the process of acylation of internal lysine residues by 14–18 carbon fatty acids is conserved among several RTX toxins, including E. coli HlyA (Lim et al, 2000; Ludwig et al, 1996) and Bordetella pertussis adenylate cyclase toxin (CyaA; Hackett, Guo, Shabanowitz, Hunt, & Hewlett, 1994; Masin et al, 2005). Acylation of the RTX toxins has been demonstrated to be required for host cell toxicity (Basar, Havlicek, Bezouskova, Hackett, & Sebo, 2001; Fong et al, 2011; Masin et al, 2005; Stanley, Packman, Koronakis, & Hughes, 1994), but the exact role of these hydrocarbon chains in host cell toxicity have not been rigorously tested, until recently when O’Brien et al demonstrated, using a comprehensive mass spectrometry‐based approach, that the acyl chains of CyaA affect toxin folding and stability (O’Brien et al, 2019). Future work may demonstrate a similar role in other RTX toxins, including LtxA.…”
Section: Ltxa Expression/secretionmentioning
confidence: 99%
“…Importantly, a significant amount of heterogeneity was observed in the acylation patterns of LtxA (Fong et al, 2011), but the process of acylation of internal lysine residues by 14–18 carbon fatty acids is conserved among several RTX toxins, including E. coli HlyA (Lim et al, 2000; Ludwig et al, 1996) and Bordetella pertussis adenylate cyclase toxin (CyaA; Hackett, Guo, Shabanowitz, Hunt, & Hewlett, 1994; Masin et al, 2005). Acylation of the RTX toxins has been demonstrated to be required for host cell toxicity (Basar, Havlicek, Bezouskova, Hackett, & Sebo, 2001; Fong et al, 2011; Masin et al, 2005; Stanley, Packman, Koronakis, & Hughes, 1994), but the exact role of these hydrocarbon chains in host cell toxicity have not been rigorously tested, until recently when O’Brien et al demonstrated, using a comprehensive mass spectrometry‐based approach, that the acyl chains of CyaA affect toxin folding and stability (O’Brien et al, 2019). Future work may demonstrate a similar role in other RTX toxins, including LtxA.…”
Section: Ltxa Expression/secretionmentioning
confidence: 99%
“…At sublytic concentrations, RTX toxins bind to β 2 -integrins and induce signaling cascades leading to apoptosis that results in inflammation, tissue lesions, and, finally, to disease [22][23][24][25][26][27]. Initial contact and binding of RTX proteins with their targets were shown to require acylation of two specific lysine sites that leads to a conformational stabilization of the protein and Ca 2+ binding at the glycine-rich nonapeptide repeats [28][29][30][31].…”
Section: Avxmentioning
confidence: 99%
“…The purity of CyaA batches is higher than 90% as judged by SDS PAGE analysis and contained less than 1 EU of LPS/μg of protein as determined by a standard LAL assay (Lonza). Finally, CyaA is refolded into a urea-free, monomeric and functional holo-state [31,32]. The refolding efficiency is around 40±5% (population monomer / total population of proteins).…”
Section: Introductionmentioning
confidence: 99%